2014
DOI: 10.2319/062613-474.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of soft tissue chin thickness in adult patients with various mandibular divergence patterns

Abstract: Objective: To evaluate the association between soft tissue at the chin (STC) thickness and mandibular divergence. Materials and Methods: Nongrowing patients seeking orthodontic treatment (n 5 190; 113 women and 77 men), who had an average age of 26.94 years (range 5 18.10-53.50 years), were stratified in four subgroups based on cephalometric mandibular plane inclination to anterior cranial base (MP/SN): low 5 MP/SN # 27u (n 5 48); medium-low 5 27u , MP/SN # 32u (n 5 60); medium-high 5 32u , MP/SN , 37u (n 5 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
4
17
1
4
Order By: Relevance
“…The statistically significant differences were found at pogonion (P <0.001), gnathion (P<0.001) for both men and women and at Menton (P=0.005) and (P<0.001) for men and women respectively. The difference between this study with previous studies (Macari and Hanna, 2013;Celikoglu et al, 2015) might be due to racial and ethnic groups. Hyperdivergent patients have deficient chin which required advancement genioplasty in comparison with the hypodivergent patients which do not require advancement genioplasty.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The statistically significant differences were found at pogonion (P <0.001), gnathion (P<0.001) for both men and women and at Menton (P=0.005) and (P<0.001) for men and women respectively. The difference between this study with previous studies (Macari and Hanna, 2013;Celikoglu et al, 2015) might be due to racial and ethnic groups. Hyperdivergent patients have deficient chin which required advancement genioplasty in comparison with the hypodivergent patients which do not require advancement genioplasty.…”
Section: Discussioncontrasting
confidence: 55%
“…A previous study which evaluated the soft chin thickness in adult patients with various mandibular divergence pattern, showed that the values of soft tissue chin thickness was statistically significant only at point gnation for both men and women (Macari and Hanna, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have also been carried out to assess the soft tissue thickness in adult patients with different vertical growth patterns (16,17). In our study, we also used Holdaway (15) analysis because it presents the soft tissue more in details with simplicity and directness in mind, and it is widely used for evaluation of soft tissue profiles.…”
Section: Discussionmentioning
confidence: 99%
“…9 The power analysis showed that 19 patients were needed in each group. To increase the power of the study, more patients were included in each group.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been almost neglected for patients with different vertical growth patterns. A bibliographic search in Medline using PubMed and the key words ''soft tissue,'' ''soft tissue thickness,'' ''facial profile,'' and ''vertical growth pattern'' showed that there has been only one study 9 investigating the association between soft tissue chin thickness and different vertical growth patterns. Within the limitations of that study, 9 which was performed on cephalometric lateral films, the soft tissue thickness values were thinner in the high-angle group than in the other groups.…”
Section: Introductionmentioning
confidence: 99%